2009
DOI: 10.1007/s11892-009-0061-2
|View full text |Cite
|
Sign up to set email alerts
|

Low-carbohydrate diets: An update on current research

Abstract: The diabetes and obesity epidemics have stimulated research to assess the benefits and potential risks of low-carbohydrate diets. Carbohydrate comprises less than 45% of calories in carbohydrate-restricted diets, but very low carbohydrate ketogenic diets may restrict carbohydrate to 20 g initially with variability in the carbohydrate level subsequently. Some research suggests that low-carbohydrate diets may achieve better early weight loss than comparison diets higher in carbohydrate. Studies of up to 1 year s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
0
13
1
3
Order By: Relevance
“…Because ketogenic lowcarbohydrate, high-fat (LC-HF) diets have proven efficiency in the management of epilepsy, it has been suggested that other neurological diseases such as Alzheimer's and Parkinson's disease might also respond well to treatment with ketogenic LC-HF diets (50). Several dietary intervention trials in overweight subjects reported that LC-HF diets exert health benefits by inducing weight loss (1,42,51). The concept of dieting by use of LC-HF diets has been largely promoted in past years (11), and these diet concepts are often known under the synonym "Atkins'-style" diets.…”
mentioning
confidence: 99%
“…Because ketogenic lowcarbohydrate, high-fat (LC-HF) diets have proven efficiency in the management of epilepsy, it has been suggested that other neurological diseases such as Alzheimer's and Parkinson's disease might also respond well to treatment with ketogenic LC-HF diets (50). Several dietary intervention trials in overweight subjects reported that LC-HF diets exert health benefits by inducing weight loss (1,42,51). The concept of dieting by use of LC-HF diets has been largely promoted in past years (11), and these diet concepts are often known under the synonym "Atkins'-style" diets.…”
mentioning
confidence: 99%
“…Multiple other studies have found that, even though a low-carbohydrate diet achieved greater weight loss at 6 months compared to a low-fat diet, the difference in weight loss was not significant at 1 year [30,31,32,33,34,35,36]. Popular low-carbohydrate diets include the Atkins diet, Bernstein diabetes diet, Caveman diet, Protein Power diet, Sonoma diet, South Beach diet, Sugar Busters diet, Zone diet, and others [35]. The effects of a low-carbohydrate diet on LDL, HDL, triglycerides, and glycemic control were not consistent in various trials and meta-analyses [35].…”
Section: The Role Of Diet In the Treatment Of Obesitymentioning
confidence: 99%
“…Popular low-carbohydrate diets include the Atkins diet, Bernstein diabetes diet, Caveman diet, Protein Power diet, Sonoma diet, South Beach diet, Sugar Busters diet, Zone diet, and others [35]. The effects of a low-carbohydrate diet on LDL, HDL, triglycerides, and glycemic control were not consistent in various trials and meta-analyses [35]. …”
Section: The Role Of Diet In the Treatment Of Obesitymentioning
confidence: 99%
“…There is also a number of expert briefings and meta-analyses conducted in recent years, which has identified the importance of the diet in the treatment of diabetes and for metabolic factors associated with different risk factors [52][53][54] .…”
Section: Introductionmentioning
confidence: 99%